A multi-omics and human biomonitoring approach to assessing the effectiveness of fortified balanced energy–protein supplementation on maternal and newborn health in Burkina Faso: A study protocol - Bastos-Moreira, Yuri; Ouédraogo, Lionel; Boevre, Marthe de; Argaw, Alemayehu; Kok, Brenda de; Hanley-Cook, Giles T.; Deng, Lishi; Ouédraogo, Moctar; Compaoré, Anderson; Tesfamariam, Kokeb; Ganaba, Rasmané; Huybregts, Lieven; et al. (MDPI, 2023)
Fortified balanced energy–protein (BEP) supplementation is a promising intervention for improving maternal health, birth outcomes and infant growth in low- and middle-income countries. This nested biospecimen sub-study aimed to evaluate the physiological effect of multi-micronutrient-fortified BEP supplementation on pregnant and lactating women and their infants. Pregnant women (15–40 years) received either fortified BEP and iron–folic acid (IFA) (intervention) or IFA only (control) throughout pregnancy. The same women were concurrently randomized to receive either a fortified BEP supplement during the first 6 months postpartum in combination with IFA for the first 6 weeks (i.e., intervention) or the postnatal standard of care, which comprised IFA alone for 6 weeks postpartum (i.e., control). Biological specimens were collected at different timepoints. Multi-omics profiles will be characterized to assess the mediating effect of BEP supplementation on the different trial arms and its effect on maternal health, as well as birth and infant growth outcomes. The mediating effect of the exposome in the relationship between BEP supplementation and maternal health, birth outcomes and infant growth were characterized via biomonitoring markers of air pollution, mycotoxins and environmental contaminants. The results will provide holistic insight into the granular physiological effects of prenatal and postnatal BEP supplementation.